2013
DOI: 10.1002/jgt.21780
|View full text |Cite
|
Sign up to set email alerts
|

Dirac's Condition for Completely Independent Spanning Trees

Abstract: Two spanning trees T1 and T2 of a graph G are completely independent if, for any two vertices u and v, the paths from u to v in T1 and T2 are internally disjoint. In this article, we show two sufficient conditions for the existence of completely independent spanning trees. First, we show that a graph of n vertices has two completely independent spanning trees if the minimum degree of the graph is at least n/2. Then, we prove that the square of a 2‐connected graph has two completely independent spanning trees. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 5 publications
(10 reference statements)
0
24
0
2
Order By: Relevance
“…These conditions are based on the sufficient conditions for hamiltonicity: Dirac's condition [25] and Ore's condition [26]. The Dirac's condition has been generalized to more than two trees [27]- [29] and has been independently improved [28], [29] for two trees.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…These conditions are based on the sufficient conditions for hamiltonicity: Dirac's condition [25] and Ore's condition [26]. The Dirac's condition has been generalized to more than two trees [27]- [29] and has been independently improved [28], [29] for two trees.…”
Section: Related Workmentioning
confidence: 99%
“…We placed 50 nodes uniformly, then we searched for (a lower bound on) the number of CISTs and its upper bound, for transmission range values r in [20,25,30,35,40,45]. We repeated the measurements for 10 different simulated networks.…”
Section: Impact Of the Transmission Rangementioning
confidence: 99%
“…Hasunuma [8] conjectured that there are k CISTs in any 2k-connected graph and showed the NP-completeness for determining the existence of two CISTs in an arbitrary graph G. So far the study related to CISTs has received less attention except for [1], [8]- [10]. Araki [1] showed that a graph G of n vertices has two CISTs if the minimum degree of G is at least n/2, and the square of a 2-connected graph has two CISTs.…”
Section: Introductionmentioning
confidence: 99%
“…Hasunuma [8] conjectured that there are k CISTs in any 2k-connected graph and showed the NP-completeness for determining the existence of two CISTs in an arbitrary graph G. So far the study related to CISTs has received less attention except for [1], [8]- [10]. Araki [1] showed that a graph G of n vertices has two CISTs if the minimum degree of G is at least n/2, and the square of a 2-connected graph has two CISTs. Hasunuma showed that there are k CISTs in the underlying graph of any k-connected line digraph L(G) [8], there are two CISTs in any 4-connected maximal planar graph [9], and there are two CISTs in the Cartesian product of any 2-connected graphs [10].…”
Section: Introductionmentioning
confidence: 99%
“…In [4], Hasunuma study the completely independent spanning trees in some graphs. Recently, Araki [1] gave a Dirac's condition characterization for the existence of completely independent spanning trees. Let G be a graph and V 1 , V 2 be two disjoint sets of vertices in G. Denote by B(V 1 , V 2 ) the bipartite graph induced by the edges with one end in V 1 and the other end in V 2 .…”
mentioning
confidence: 99%